The importance of stimulus variability when studying face processing using fast periodic visual stimulation: A novel 'mixed-emotions' paradigm. (August 2019) - Coll, Michel-Pierre; Murphy, Jennifer; Catmur, Caroline; Bird, Geoffrey; Brewer, Rebecca
Abstract: Fast Periodic Visual Stimulation (FPVS) with oddball stimuli has been used to investigate discrimination of facial identity and emotion, with studies concluding that oddball responses indicate discrimination of faces at the conceptual level (i.e., discrimination of identity and emotion), rather than low-level perceptual (visual, image-based) discrimination. However, because previous studies have utilised identical images as base stimuli, physical differences between base and oddball stimuli, rather than recognition of identity or emotion, may have been responsible for oddball responses. This study tested two new FPVS paradigms designed to distinguish recognition of expressions of emotion from detection of visual change from the base stream. In both paradigms, the oddball emotional expression was different from that of the base stream images. However, in the 'fixed-emotion' paradigm, stimulus image varied at every presentation but the emotion in the base stream remained constant, and in the 'mixed-emotions' paradigm, both stimulus image and emotion varied at every presentation, with only the oddball emotion (disgust) remaining constant. In the fixed-emotion paradigm, typical inversion effects were observed at occipital sites. In the mixed-emotions paradigm, however, inversion effects in a central cluster (indicative of higher level emotion processing) were present in typical participants, but not those with alexithymia (who are impaired at emotion recognition), suggesting that only the mixed-emotions paradigm reflects emotion recognition rather than detection of a lower-level visual change from baseline. These results have significant methodological implications for future FPVS studies (of both facial emotion and identity), suggesting that it is crucial to vary base stimuli sufficiently, such that simple physical differences between base and oddball stimuli cannot give rise to neural oddball responses.